KORELASI DUKUNGAN KELUARGA DAN PENGETAHUAN HIPERTENSI TERHADAP POLA HIDUP PENDERITA HIPERTENSI DI DKI JAKARTA - Puspita Hanggit Lestari; Mia Fatma Ekasari; Nur Fitri Ayu Pertiwi (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2022)
Hypertension is a disease that needs to be controlled properly so as not to cause severe complications and even death. Patients with hypertension need to maintain a healthy lifestyle in order to control blood pressure and minimize complications. Patients with hypertension need support from their families in hypertension health care. Objective: to determine the relationship between family support and knowledge of hypertension on the lifestyle of hypertensive patients and the variables that affect the lifestyle of hypertensive patients. Methods: The research design used is a cross-sectional quantitative study with a research sample of 103 respondents. The sampling technique used in this study was purposive sampling. Results: The study found that the variables of family support (40.8%), knowledge of hypertension (42.7%) and lifestyle of hypertension patients (50.5%) were in the poor category. The family support variable has a relationship with the lifestyle of people with hypertension (p value = 0.000) and the knowledge of hypertension variable has a relationship with the lifestyle of people with hypertension (p value = 0.000). The results of the coefficient analysis showed that age was 0.041, last education was 0.284, duration of hypertension was 0.573, the results of the last blood pressure examination were 0.271, knowledge of hypertension was 0.000 and family support was 0.000. Conclusion: There is a relationship between family support and knowledge with the lifestyle of patients with hypertension. Variables that affect the lifestyle of patients with hypertension are gender, knowledge of hypertension and family support. The results of the study are expected to help determine the appropriate health promotion program for people with hypertension by involving the family in hypertension health care.